2018
DOI: 10.1109/tnsre.2018.2832055
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Electrical Stimulation Efficacy in Degenerated Retina: Stimulus Waveform Design in a Multiscale Computational Model

Abstract: A computational model of electrical stimulation of the retina is proposed for investigating current waveforms used in prosthetic devices for restoring partial vision lost to retinal degenerative diseases. The model framework combines a connectome-based neural network model characterized by accurate morphological and synaptic properties with an admittance method model of bulk tissue and prosthetic electronics. In this model, the retina was computationally "degenerated," considering cellular death and anatomical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 62 publications
0
51
0
Order By: Relevance
“…The results showed that retinal ganglion cell stimulation thresholds do not vary much after the early stages of retinal degeneration. The simulation of the proposed asymmetric waveforms also showed the ability to improve the control of the ganglion cell firing via electrical stimulation [41].…”
Section: Computational Model Of Electrical Stimulation Of the Retinamentioning
confidence: 90%
See 4 more Smart Citations
“…The results showed that retinal ganglion cell stimulation thresholds do not vary much after the early stages of retinal degeneration. The simulation of the proposed asymmetric waveforms also showed the ability to improve the control of the ganglion cell firing via electrical stimulation [41].…”
Section: Computational Model Of Electrical Stimulation Of the Retinamentioning
confidence: 90%
“…To restore vision in patients with degenerative diseases, retinal prosthetic devices have been developed, which through electrical stimulation of the local regions of retinal tissue, bring together spatiotemporal patterns to represent the patient-facing image. These devices have proven to be effective, which has led to the design of various types of devices, many of which are in trials and some are already in the market [41]. For example, Argus II by Second Sight Medical Products Inc. (Sylmar, CA, USA) is already in clinical trials and has been shown to provide patients considerable visual perception to the extent that subjects can recognize objects and differentiate letters.…”
Section: Gap Junctionsmentioning
confidence: 99%
See 3 more Smart Citations